2018
DOI: 10.2217/pgs-2018-0093
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk Factors for VIPN in Childhood Acute Lymphoblastic Leukemia Patients Identified Using Whole-Exome Sequencing

Abstract: Variants in SYNE2, MRPL47 and BAHD1 genes are putative new risk factors for VIPN in childhood acute lymphoblastic leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 53 publications
0
41
0
3
Order By: Relevance
“…Also several haplotypes were associated with neurotoxicity. Abaji et al (2018) screened retrospectively WES data of ALL patients to find possible new gene variants which could be associated with VIPN. In this study, three new gene variants are association with VIPN: Spectrin Repeat Containing Nuclear Envelope Protein 2 (SYNE2) (rs2781377), Mitochondrial Ribosomal Protein L47 (MRPL47) (rs10513762) and Bromo Adjacent Homology Domain Containing 1 (BAHD1) (rs3803357).…”
Section: Pharmacodynamics Stability Of Microtubules and Neurotoxicitmentioning
confidence: 99%
See 1 more Smart Citation
“…Also several haplotypes were associated with neurotoxicity. Abaji et al (2018) screened retrospectively WES data of ALL patients to find possible new gene variants which could be associated with VIPN. In this study, three new gene variants are association with VIPN: Spectrin Repeat Containing Nuclear Envelope Protein 2 (SYNE2) (rs2781377), Mitochondrial Ribosomal Protein L47 (MRPL47) (rs10513762) and Bromo Adjacent Homology Domain Containing 1 (BAHD1) (rs3803357).…”
Section: Pharmacodynamics Stability Of Microtubules and Neurotoxicitmentioning
confidence: 99%
“… Abaji et al. (2018) screened retrospectively WES data of ALL patients to find possible new gene variants which could be associated with VIPN.…”
Section: Role Of Pharmacogenetic Variations In Chemotherapeutic Relatmentioning
confidence: 99%
“…In a cohort of 237 children with ALL, Abaji et al 66 identified 2 genetic polymorphisms that put patients receiving chemotherapy at risk for peripheral neurotoxicity. The first polymorphism is rs2781377 in spectrin repeat-containing nuclear envelope protein 2 (SYNE2) , which codes for nesprin, a nuclear envelope spectrin repeat protein that maintains cellular cytoskeleton.…”
Section: Variants Associated With All Treatment Toxicitiesmentioning
confidence: 99%
“… 74 , 161 Results were however not replicated in two other studies. 162 , 163 More recently whole-exome sequencing of DNA from 240 European children with ALL revealed an association between four variants in four genes ( BAHD1 rs3803357, MRPL47 rs10513762, SYNE2 rs2781377 , and CDH2 rs1944294 ) with VINC-related neuropathy, 66 however these results were not yet validated in other populations.…”
Section: Evidence For the Individualization Of Treatment Regimensmentioning
confidence: 99%
“…Recently, a whole-exome sequencing analysis combined with an exome-wide association study was performed to find out genetic risk factors for VCR-related neurotoxicity [64]. The study identified two variants significantly associated with an increased risk of high-grade VCR-related neurotoxicity, rs2781377 in the SYNE2 gene and rs10513762 in the MRPL47 gene.…”
Section: Vincristinementioning
confidence: 99%